Male Migration, Female Perdition: Narratives of Economic and Reproductive Impotence in a Haitian Transnational Community - Richman, Karen (Anthropologica, 2012)
Distant members of a Haitian transnational com munity are creatively adapting an old reproductive afflic tion to mediate new, arduous experiences of prolonged con jugal separation and frustrated hopes of socio-economic advance. Perdition (pèdisyon), meaning repressed pregnan cy, plays out in social dramas enacted between Léogâne and Florida, sites inhabited by impoverished migrant labour pro ducers at home and their hopeful emissaries abroad. The dra mas ensuing from repressed pregnancy span not only national boundaries but also religious borders dividing Protestants from Catholics.